A Refresh Of The Institutional Mindset In Campus-Based Islamic Broadcasting Through The Synergy Of Da'wah - Farid, Ahmad Salman; Ardiansyah, Muhammad; Ibrahim, Abubakar Tijjani (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study explores the institutional culture and communicative practices of campus-based Islamic broadcasting units, focusing on how they can be revitalized through a synergistic approach to da’wah. Traditional preaching methods, while religiously grounded, often fail to engage contemporary Muslim youth who prefer participatory and dialogic communication. Therefore, this study argues for an institutional refresh that integrates media literacy, creative collaboration, and intergenerational dialogue. Using a qualitative multi-case study approach, data was gathered through in-depth interviews, focus group discussions, and participatory observation in three leading Islamic-based campuses across Indonesian universities. The analysis employed grounded theory techniques and was informed by dialogic communication models and participatory media frameworks. Findings indicate a strong disconnect between institutional norms and student communicators’ expectations. Units that permitted co-creation and interdisciplinary collaboration saw higher levels of engagement and relevance in their da’wah content. In contrast, rigid units experienced stagnation and disengagement. The research also reveals the importance of shifting from sermon-based approaches to conversational, issue-driven, and emotionally resonant storytelling. The study suggests a reframing of da’wah as a communicative practice rooted in mutual learning, cultural relevance, and organizational openness. By aligning Islamic values with adaptive media strategies, campus broadcasting units can become vibrant centers of youth-led spiritual discourse and ethical media production. Institutional change, however, requires both structural reform and a new mindset centered on trust, creativity, and pluralism. Keywords: Campus Da’wah; Institutional Culture; Islamic Broadcasting; Participatory Communication; Youth Engagement